PEMBUATAN BUBUK KONSENTRAT PROTEIN KELAPA (BLONDO) SEBAGAI SUSU RENDAH LEMAK MENGGUNAKAN ALAT PENGERING BEKU VAKUM - Afrizal, Muhammad; HC, Fadarina; Purnamasari, Indah (Politeknik Negeri Sriwijaya, 2020)
Coconut protein concentrate (blondo) can be used as a milk product because it has a high nutrient and mineral content, so it can be used as an affordable alternative to formula milk to treat malnutrition in Indonesia. Coconut protein concentrate (blondo) is packaged in powder form, so that the product lasts longer. Vacuum freeze dryer is suitable for drying coconut protein concentrate (blondo) which is susceptible to high temperatures to avoid denaturation of its protein content. Coconut protein concentrate (blondo) with mass variations of 40 and 50 gr was put into a freeze dryer to be dried with variations in vacuum pressure at 64, 67, 70 and 73 cmHg. The comparison of the quality of each product will be viewed from the moisture, protein and fat content. Based on the results of the analysis obtained, at a vacuum pressure of 73 cmHg with a mass of 50 gr has the best quality results with a moisture content of 4.99%, a protein content of 23.84% and a fat content of 10.90%. Thus, the greater the vacuum pressure, the better the quality of the product.